The Mesoamerican Biological Corridor - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This is a Regional Program Review (RPR) of the World Bank's support for the MBC. The review is framed around an assessment of five Global Environment Facility (GEF)-financed World Bank implemented projects in Costa Rica, Honduras, Mexico, Nicaragua and Panama that had the common objective of consolidating the Mesoamerican Biological Corridor (MBC). It also reports on the achievements of trust fund activities, financed by the Bank Netherlands Partnership Program (BNPP), that were implemented parallel to the GEF/World Bank projects. The MBC is a land-use planning system that spans Central America and Mexico. It is designed to promote the conservation and sustainable use of the region's natural resources. The overall objective of the Bank's MBC projects of consolidating the MBC was highly relevant. Although the Central American land bridge is very small, it is estimated to be home to 12 percent of the world's known species. It harbors approximately 24,000 species of vascular plants and over 500 species of mammals, many of which are endemic. The MBC derives its legitimacy from the endorsement it received at the Central American heads of state summit in 1997.